Arthritogenic alphaviruses: new insights into arthritis and bone pathology. Issue 1 (January 2015) - Chen, Weiqiang; Foo, Suan-Sin; Sims, Natalie A.; Herrero, Lara J.; Walsh, Nicole C.; Mahalingam, Suresh
Highlights Enhanced osteoclastogenesis and bone loss take place during arthritogenic alphavirus infection. There is strong interplay between immune responses in alphaviral arthritis and bone health. There is a potential risk of alphavirus infection exacerbating underlying inflammatory arthritis. Targeting osteotropic factors may be efficacious in treating alphaviral-induced bone loss.